306PEfficacy and safety of apatinib in heavily pretreated metastatic adenocarcinoma of the head and neck. (24th November 2019) - Gui, L; He, X
Abstract: Background: The optimal therapy for adenocarcinoma of the head and neck with distant metastasis is very limited and controversial. Although antiangiogenic therapy is eﬀective in advanced lung, colon, hepatic, and renal carcinomas, limited is known about its value in the carcinoma of the head and neck. Apatinib, an oral, highly potent tyrosine kinase inhibitor targeting vascular endothelial growth factor receptor 2 (VEGFR-2), has been proven to be effective for the treatment of a broad range of advanced solid tumors. This prospective phase II study (NCT02989259) aims to investigate the efficacy and safety of apatinib in heavily pretreated patients with metastatic adenocarcinoma of the head and neck. Methods: This study enrolled patients with adenocarcinoma of the head and neck, who failed in the metastatic setting at least one prior chemotherapy regimen. The primary end point was progression free survival (PFS). Secondary end points included objective response rate, disease control rate, overall survival (OS), and safety. Patients were treated with apatinib 500 mg daily until disease progression or the occurrence of intolerable toxicity. Efficacy was assessed every 8 weeks. Results: From December 2016 to January 2019, twenty patients were enrolled, including 13 males and 7 females, with a median age of 61 years (26-79). The median number of previous chemotherapy regimens for the metastatic diseases was 2 (1-3). Partial response was achieved by 5 (25%) patients and stable disease exhibited by 14 (70%) patients.The median PFS and OS were 7.5 and 11.0 months, respectively. The most common adverse events (AEs) of all grade were secondary hypertension (n = 16), proteinuria(n = 10), hyperbilirubinemia (n = 10), nausea (n = 6), fatigue (n = 5) and hand-foot syndrome (n = 4). Grade 3/4 AEs were hypertension (n = 4), oral microsites (n = 3), and thrombocytopenia (n = 1). No grade 4 or 5 AE was observed in the study. Conclusions: Our results indicated that apatinib exhibited objective efficacy in heavily pretreated, metastatic adenocarcinoma of the head and neck with a manageable toxicity profile. Apatinib can be considered as a treatment option for adenocarcinoma of the head and neck with metastatic diseases. Clinical trial identification: The trial protocol number is NCT02989259. And release date is December 2016. Legal entity responsible for the study: CAMS & PUMC, National Cancer Center, Cancer Hospital. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.